An Analysis of Factors Affecting use of Computer Technology in Rural Secondary Schools by ODL Students Who are Secondary School Teachers in Mbire District of Mashonaland Central Province of Zimbabwe - Rittah Kasowe (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
There is compelling evidence that incorporating ICT into teaching and learning improves students’ academic performance. Its benefits occur across all socio-economic classes. Despite its relevance, ODL students who must use ICT in their university studies as well as in teaching and learning appear to puts a greater importance on its implementation. As a result, the purpose of this study was to look into the characteristics that influence ODL students who are studying at an Open and Distance Learning university while also teaching in secondary schools.The study used a descriptive survey design and a mixed methods approach. The population of the study comprised 78 ODL students who are secondary school teachers. The 40 respondents and 5 participants were chosen using a combination of systematic random sampling and purposive sampling.The questionnaire, interview, and observation procedures were used to gather and create data. Quantitative data was presented using frequency tables, graphs, and descriptive statistics, while qualitative data was presented using transcripts and themes. The analysis discovered that material and infrastructure resources are in short supply.The teachers/facilitators do not have the necessary expertise. Teachers use computers to enhance their professional job to a limited extent. Teachers’ attitudes towards teaching using computers have a bearing on implementation of the innovation. Schools are having difficulty affording to outsource computer equipment and build computer labs due to financial constraints.As a result, the study suggests that ODL students participate in in-service training sessions or even take computer short courses. Out dated computers, need to be replaced with modern ones which have more capacity. Schools should be subsidised by the government to acquire and built infrastructure Schools and the community need to be staff developed on ways of income generation.